Perilaku Penggunaan E Wallet Oleh Generasi Z Dalam Pembayaran Aplikasi Transportasi Online - Fahlevi, Renza; Wang, Thalia; Sinambela, Fitriana Aidnilla (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
Currently, the use of e-wallet applications has increased, especially after the Covid-19 pandemic. The use of e-wallet applications has become popular for financial transactions and payments for online applications such as Grab and Gojek. The purpose of this research is to test the relationship between the variables such as perceived usefulness, social influence and perceived security on attitude toward using and intention to use e-wallet for generation Z users from a payment online transportation transaction perspective. This study is a quantitative study. The number of research respondents was 205 respondents who were e-wallet users aged 11 to 26 years. Data collection was carried out by distributing questionnaires via google form. Research data was processed using by PLS application. The results of the research showed that the variables perceived usefulness and perceived security are variables that influence attitude using toward and intention to use e-wallet, but other variables, namely social influence do not affect attitude using toward and intention to use e-wallet.